The dialect of Marvão: contributions for its study - Teresa Susana Bangala Simão (Revista de Filología Románica, 2013)
This article is a synthesis of the ongoing research about the border dialect of Marvão, a district in the north-west of Alentejo which borders Valência de Alcântara in Extremadura, Spain. Firstly it presents a brief characterization of the territory in study; secondly it shows how the dialect of Marvão fits in the overwiew of Portuguese dialects and it presents its main features under the phonetic-phonological, morphological, syntactic and lexical viewpoints. Although this dialect presents many of the characteristics identified by the linguistics of the 20th century on this dialectical region, it is distinguished due to some particularities which make it different from other dialects of the border districts.